Influência da geometria sobre o rendimento de bocais injetores de turbinas tesla no escoamento compressível supersônico - Neckel, Andre Luis (My University, 2014)
Nozzles with convergent-divergent geometry are designed and manufactured for the establishment of supersonic flows. The main objective of this work is to verify the variation of isentropic efficiency depending on the geometry of the diverging section of the nozzle. These nozzles are designed with geometries suitable for installation in Tesla turbines. Ten nozzles are designed using two distinct considerations: one-dimensional isentropic flow and two-dimensional isentropic flow (characteristic method). The flow nozzles were analyzed using air as the working fluid. The design of the nozzles was conducted to an inlet pressure of 500 kPa of the working fluid in the converging section. Moreover, the nozzles have been designed for two mass flow rates: 55 to 70 kg/h. From the tests was found a good agreement between the experimental results and the values predicted by theory. In all nozzles designed supersonic speeds were observed in their different sections. For both mass flows used, Mach number ranged between 1.50±0.1 and 1.58±0.1 in the exit of the diverging section were obtained. In the design condition nozzles designed from the characteristic method exhibited higher isentropic efficiencies isentropic. Accordingly of these condition the highest isentropic eficiencies obtained were 87.23±0.5% from mass flow rate of 55kg/h and 87.73±0.5% from 70 kg/h. From the Schilieren technique was possible to prove the presence of shock waves in the discharge nozzles, which contribute to the irreversibilities associated with the flow. The results show that nozzles designed appropriately can increase the overall efficiency (turbine + nozzle) of cycles which use turbines Tesla.
Bocais com geometria convergente-divergente foram projetados e fabricados para o estabelecimento de escoamentos supersônicos. O objetivo principal do presente trabalho é verificar a variação da eficiência isoentrópica em função da geometria da seção divergente dos bocais. Os referidos bocais foram projetados com geometrias apropriadas para a sua instalação em turbinas tipo Tesla. Dez bocais foram projetados empregando duas considerações distintas: escoamento isoentrópico unidimensional e escoamento isoentrópico bidimensional (método das características). O escoamento nos bocais foi analisado utilizando ar como fluido de trabalho. O projeto dos bocais foi conduzido para uma pressão de entrada do fluido de trabalho na seção convergente de 500 kPa. Além disto, os bocais foram projetados para duas taxas mássicas distintas: 55 e 70 kg/h. A partir dos ensaios foi verificada uma boa concordância entre os resultados experimentais e os valores preditos pela teoria. Em todos os bocais projetados foram observadas velocidades supersônicas em suas seções divergentes. Para ambas as taxas mássicas de projeto o número de Mach variou entre 1,50±0,1 e 1,58±0,1 na saída da seção divergente. Nas condições de projeto os bocais projetados a partir do método das características apresentaram eficiências isoentrópicas mais elevadas. Nestas condições as maiores eficiências isoentrópicas obtidas foram de 87,23 ±0,5 % para a taxa mássica de 55kg/h e de 87,73±0,5 % para a taxa mássica de 70 kg/h. A partir da técnica de Schilieren foi possível comprovar a presença de ondas de choque na descarga dos bocais, que contribuem para as irreversibilidades associadas ao escoamento.
Keywords: Materiais - Testes; Geometria